2014
DOI: 10.5005/jp-journals-10005-1264
|View full text |Cite
|
Sign up to set email alerts
|

Biological Restoration in Pediatric Dentistry: A Brief Insight

Abstract: ABSTRACT%Dental caries is the most prevalent disease in humans, especially during early childhood. The restoration of such an extensive carious lesion should be done properly to reestablish their anatomy and hence their masticatory, phonetic, esthetic and space-maintainer functions in the dental arches. The consequences of premature loss of primary teeth are well known, namely the loss of vertical dimension of occlusion, tongue thrusting and mouth breathing habits, which can be the sources of future malocclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Microbiological culturing and scanned electron microscope (SEM) analysis was has verified that humid -steam vapor has the potential to eliminate microorganisms. 10 In the present study, the enamel blocks incorporated appliances were sterilized in an autoclave at 210° C for 30 minutes and delivered.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiological culturing and scanned electron microscope (SEM) analysis was has verified that humid -steam vapor has the potential to eliminate microorganisms. 10 In the present study, the enamel blocks incorporated appliances were sterilized in an autoclave at 210° C for 30 minutes and delivered.…”
Section: Discussionmentioning
confidence: 99%
“…Tambien menciona que la caída prematura de las piezas deciduas tiene como consecuencia problemas para la función masticatoria, fonación, lo que altera la secuencia de erupción de las piezas dentarias permanentes causando maloclusiones, apiñamientos, piezas impactadas, línea media desviada y asimetría facial, problemas que van a afectar tanto a nivel de desarrollo físico, emocional y psicológico. MD Indira et al (2014) relata que con la creciente concienciación general, muchos niños incluso de tan solo 3 años empiezan a ser conscientes de su apariencia siendo que independientemente de la cantidad de estructura dentaria este afectada, una buena rehabilitación sería uno de los objetivos más importantes.…”
Section: Discussionunclassified
“…In the present study, it was observed that most of the patients were either neutral, satisfied, or very satisfied with biological crowns, however, few patients/parents’ dissatisfactions were also observed, because biological restoration did not match adjacent teeth color. 23 …”
Section: Discussionmentioning
confidence: 99%
“…25 Although patient/parental dissatisfaction can be attributed to the fact that there was difficulty in obtaining biological crown matching color with adjacent tooth color and also, having tooth from other people's teeth in their mouth might not be a pleasant idea for some patients. 23 …”
Section: Discussionmentioning
confidence: 99%